2009
DOI: 10.1007/s00068-009-8165-6
|View full text |Cite
|
Sign up to set email alerts
|

A New Injectable Brushite Cement: First Results in Distal Radius and Proximal Tibia Fractures

Abstract: The tested material showed good outcome in the majority of patients and adequate resorption characteristics, even in the case of extravasation. Stable internal fixation, sufficient bone quality, and no contact between the cement and joint are essential requirements for chronOS Inject, which can be considered as an alternative to existing augmentation materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…In addition, it can effectively encourage angiogenesis by upregulating nitric oxide synthase (NOS) leading to increased VEGF production [36]. In some cases, leakage of the brushite cement has been observed into the adjacent tissues, but it is ultimately resorbed without causing any significant complications [51]. Similar observations were also noted in microstructural evaluation using SEM.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, it can effectively encourage angiogenesis by upregulating nitric oxide synthase (NOS) leading to increased VEGF production [36]. In some cases, leakage of the brushite cement has been observed into the adjacent tissues, but it is ultimately resorbed without causing any significant complications [51]. Similar observations were also noted in microstructural evaluation using SEM.…”
Section: Discussionmentioning
confidence: 86%
“…This phase conversion effect has not been observed with monetite biomaterials and they have a greater amount of new bone formation and infiltration associated with them [333]. Resorbable and injectable brushite cements have been investigated for use in treating metaphyseal bone defects [136,340]. Brushite cements have also been used for treatment of fractures in the tibial plateau [136] and distal metaphysic bone [340].…”
Section: Biodegradable Materialsmentioning
confidence: 99%
“…Besides, other successful attempts have been made to use these formulations for calcaneal fractures [509], hip fractures [510,511], augmentation of osteoporotic vertebral bodies [512], distal radius fractures [513], tibial plateau fractures [33,[513][514][515][516][517], restoration of pedicle screw fixation [518,519], reinforcement of thoracolumbar burst fractures [520], cancellous bone screws [521,522], in wrist arthrodesis [523] and for fixation of titanium implants [524]. A recent study on a cement augmentation of the femoral neck defect might be found elsewhere [525].…”
Section: Orthopaedic Applicationsmentioning
confidence: 99%